Identification of biotransformation products of organophosphate ester from various aquatic species by suspect and non-target screening approach. (15th July 2021) - Choi, Yeowool; Jeon, Junho; Kim, Sang Don
Highlights: 29 biotransformation products of TPHP were identified in various aquatic species Different biotransformation pathways were determined for each aquatic species BTPs mechanisms expressed in organisms were mainly hydrolysis and hydroxylation Most BTPs were predicted less toxic than TPHP, but some were to be higher. Abstract: Organic pollutants that are introduced into the aquatic ecosystem can transform by various mechanisms. Biotransformation is an important process for predicting the remaining structures of pollutants in the ecosystem, and their toxicity. This study focused on triphenyl phosphate (TPHP), which is a commonly used organophosphate flame retardant and plasticizer. Since TPHP is particularly toxic to aquatic organisms, it is essential to understand its biotransformation in the aquatic environment. In the aquatic ecosystem, based on consideration of the producer-consumer-decomposer relationship, the biotransformation products of TPHP were identified, and their toxicity was predicted. Liquid chromatography-high resolution mass spectrometry was used for target, suspect, and non-target analysis. The obtained biotransformation products were estimated for toxicity based on the prediction model. As a result, 29 kinds of TPHP biotransformation products were identified in the aquatic ecosystem. Diphenyl phosphate was detected as a common biotransformation product through a hydrolysis reaction. In addition, products were identified by the biotransformation mechanisms of green algae, daphnid, fish, and microorganism. Most of the biotransformation products were observed to be less toxic than the parent compound due to detoxification except some products (hydroquinone, beta-lyase products, palmitoyl/stearyl conjugated products). Since various species exist in a close relationship with each other in an ecosystem, an integrated approach for not only single species but also various connected species is essential. Graphical abstract: Image, graphical abstract